Synchronous Hepatic Cryotherapy and Resection of Colonic Primary is a High Risk Procedure. Issue 6 (2000) - Cheung, D.; Morris, D. L.
Abstract : Thirteen patients underwent hepatic cryotherapy and synchronous colonic resection. Two of the nine patients developed hepatic abscess – this is a rare complication of cryotherapy alone.